2015
DOI: 10.1186/s12889-015-2359-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep duration and obesity is age- and gender-dependent in Chinese urban children aged 6–18 years: a cross-sectional study

Abstract: BackgroundInformation on the relationship between sleep duration and obesity among children in urban Guangzhou, China is limited. This study aims to examine the relationship between sleep duration and obesity in children aged 6–18 years.MethodsThe sample consisted of 11,830 children aged 6–18 years. The children were randomly selected from 13 schools in three urban districts of Guangzhou. The study was conducted from September to November 2013. The height and weight of the children were measured. Adiposity sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
54
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 37 publications
7
54
0
1
Order By: Relevance
“…This was consistent with studies done in China [39], Ghana and Uganda [22]. In contrary to the findings of this study, a study conducted in China [43] revealed that short sleep duration and sleeping in the afternoon was not associated with obesity. This discrepancy might be due to difference in sleeping habits and age of the participants.…”
Section: Discussionsupporting
confidence: 91%
“…This was consistent with studies done in China [39], Ghana and Uganda [22]. In contrary to the findings of this study, a study conducted in China [43] revealed that short sleep duration and sleeping in the afternoon was not associated with obesity. This discrepancy might be due to difference in sleeping habits and age of the participants.…”
Section: Discussionsupporting
confidence: 91%
“…There was also some evidence for gender patterning: with nine of the 103 reviewed articles reporting on sleep duration indicating the association between sleep duration and Ow/Ob as significant among boys only ; while three reported it as significant among girls only; and one reported mixed results across genders, as mentioned above …”
Section: Resultsmentioning
confidence: 90%
“…Of the 103 articles reporting on sleep duration: 86 (83%) reported a significant negative association between duration of sleep and measured weight status, where shorter sleep durations were linked with poorer weight status measures. In contrast, one study reported overweight and obesity to be higher among longer sleepers (>10 hours/night); while another study indicated mixed results, where girls with short sleep displayed higher weight status and boys with short sleep displayed lower weight status measures . Only 15 articles (14%) found no significant association between children's sleep duration and measured weight status.…”
Section: Resultsmentioning
confidence: 94%
“…En el año 2005, una encuesta realizada en ese país mostró que la duración media del sueño fue de 8,4 horas en niños de 11-12 años y menos de 7 horas en adolescentes de 16-17 años. Informes recientes de China, Australia y otros países, también indicaron una disminución de la duración del sueño entre los niños de 6 a 18 años, considerándose la corta duración del sueño como un fenómeno global 3 . La evidencia científica señala que los durmientes cortos y el aumento de la exposición a la luz artificial durante la noche son paralelo al aumento global de la prevalencia de la obesidad y los trastornos metabólicos 4 .…”
Section: Introductionunclassified